COVID-19 infection characteristics, risk factors and its potential impacts on Takayasu arteritis: a web-based survey in a large cohort - Kong, Xiufang; Wang, Jinghua; Fan, Guihua; Huang, Huijing; Sun, Ying; Chen, Huiyong; Ma, Lili; Li, Yanshan; Jiang, Lindi (Frontiers in Immunology, 2024)
Objectives: To investigate the characteristics of COVID-19 and its impact on patients with Takayasu’s arteritis (TAK). Methods: A web-based survey was administered to a TAK cohort and their co-residents in China during January 2023. Infection symptoms, post-acute sequelae of COVID-19 (PASC), potential impacts of COVID-19 on patients’ disease condition, treatment and immune-related parameters were analyzed. In addition, risk factors for COVID-19 and disease relapse after infection were explored. Results: The infection rate was significantly lower in patients with TAK than in co-residents (79.13% vs 90.67%, p=0.025). TAK patients were more prone to gastrointestinal symptoms (17.78% vs 5.88%, p=0.024), sleep problems (25.15% vs 10.29%, p=0.011), and symptoms involving more than 2 organs (58.90% vs 35.29%, p=0.001) after infection. Although only 2.45% of TAK patients were hospitalized and none progressed to life-threatening conditions, they were more likely to suffer from PASC (26.38% vs 13.24%, p=0.029), especially active patients. Active disease after the pandemic was significantly lower in infected patients than uninfected patients (21/163, 12.88% vs. 11/43, 25.58%, p=0.041). The presence of multiple system symptoms was a risk factor for active TAK after infection (OR: 3.62 [95% CI 1.06-12.31], p=0.040). Moreover, csDMARDs treatment was a risk factor for COVID-19 infection (OR: 3.68 [95% CI 1.56-8.66], p=0.002). Conclusion: Although TAK patients with COVID-19 have more acute and post-acute symptoms, there is no adverse outcome and the risk of disease relapse does not increase. Patients treated with csDMARDs may be at higher risk of infection and deserve more clinical attention.